Integrasi Teknologi dalam Pengajaran Bahasa Arab di Madrasah - Fatimah, Siti; Jumriyah, Jumriyah; Mubasyiroh, Mubasyiroh (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This research aims to expose different ways of using technology in Arabic language teaching, assess the effectiveness of technology in improving students' language skills, and discover the obstacles and supporting elements of using technology. The ultimate goal of this research is to provide practical suggestions on using technological innovations to improve the quality of Arabic language learning. This study uses a descriptive qualitative approach. This study applies a qualitative approach with a multisite type to explore the process of technology integration in Arabic language teaching in various educational institutions. Through data collection techniques such as interviews, observations, and documentation in several locations, this research seeks to uncover patterns of implementation, obstacles faced, and effective strategies that support the success of technology integration in contextualized Arabic language learning. The data is collected through classroom observations, interviews with Arabic teachers, and documentation studies on using digital learning media. Data analysis in this study was conducted qualitatively with a multisite approach, starting from the data reduction process by selecting important information from interviews, observations, and documentation in several educational institutions. The results show that learning videos, digital dictionary apps, online quizzes, and language learning platforms such as Google Classroom and Duolingo significantly increase student participation. However, unequal technology infrastructure and limited training for teachers become major problems. It is proven that using technology in Arabic language teaching increases learning effectiveness and interactivity. However, implementation relies heavily on well-prepared teachers, available infrastructure, and institutional policy support. For these innovations to be successful and sustainable, educators and technology developers must work together.